The Influence of Service Quality Perception on Trust and User Loyalty in the Gojek Application - Rizki Febiyanti; Afif Abdul; Abdul Malik Karim Amrullah; Zulfa Fahmy; Khairani Zikrinawati (Experimental Student Experiences, 2024)
The industry needs to maintain the trust and loyalty of users to ensure that their services are chosen as the primary option. Perceived service quality is one of the factors that influence trust and loyalty. Therefore, this research aims to evaluate how perceptions of service quality can affect the trust and loyalty of Gojek application users. The research method used is quantitative, with data collected using a Likert scale from 100 respondents who are students of UIN Walisongo Semarang randomly selected (random sampling). The analysis technique used is a simple correlation. The simple regression results of variable X on Y1 are 0.00, while variable X on Y2 is 0.004. It can be concluded that UIN WALISONGO Semarang students positively evaluate the service quality of Gojek and positively influence their trust and loyalty towards the application.